From Murabbi to Service Provider: The Loss of Adab and Commodification of Teachers in Indonesia’s Elite Islamic Schools - Agung Tri Prasetia; Yan Guspriadi; Habib Hidayatullah (International Journal of Applied Counseling and Social Sciences, 2025)
This article explores the transformation of teachers in Indonesia's elite Islamic schools from moral exemplars (murabbi) to service providers, set against processes of middle-class social reproduction. Drawing on Pierre Bourdieu's theory of capital conversion and symbolic violence, complemented by Syed Muhammad Naquib al-Attas's concept of the "loss of adab"—the erosion of knowledge's proper moral hierarchy—the study reveals how high-fee institutions (annual costs often exceeding IDR 70–300 million in 2025, as seen in schools like X Islamic School and modern pesantren) prioritize quantifiable religious credentials (tahfidz, MTQ victories, Arabic fluency) as markers of class distinction. Through qualitative multiple case studies of five urban schools, involving interviews with parents, teachers, administrators, and alumni, findings highlight teachers' displacement: evaluated via KPIs and parental surveys, they internalize subordinated roles, fracturing their exemplary authority. This commodification perpetuates performative piety among students while eroding authentic adab transmission. The paradox is stark: institutions meant to foster spiritual formation instead reinforce stratification, producing generations adept in religious forms but often deficient in inner virtue—a subtle de-islamization masked as excellence.